2013
DOI: 10.4037/ajcc2013973
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Timing of Transfer Out of the Intensive Care Unit

Abstract: Water-rich regions in Earth's deeper mantle are suspected to play a key role in the global water budget and the mobility of heat-generating elements. We show that ice-VII occurs as inclusions in natural diamond and serves as an indicator for such water-rich regions. Ice-VII, the residue of aqueous fluid present during growth of diamond, crystallizes upon ascent of the host diamonds but remains at pressures as high as 24 gigapascals; it is now recognized as a mineral by the International Mineralogical Associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 43 publications
(41 reference statements)
0
24
0
Order By: Relevance
“…Timing seemed to be a critical point, and this is confirmed in a study by Garland and Connors (2013). Their study indicated that 30-day mortality increased not only if the patients had to leave earlier than planned from the ICU but also if the transfer was delayed so they had to leave later than was optimal [29]. Our study shows that timing and competence concerning extubation and weaning procedures are essential.…”
Section: Discussionmentioning
confidence: 76%
“…Timing seemed to be a critical point, and this is confirmed in a study by Garland and Connors (2013). Their study indicated that 30-day mortality increased not only if the patients had to leave earlier than planned from the ICU but also if the transfer was delayed so they had to leave later than was optimal [29]. Our study shows that timing and competence concerning extubation and weaning procedures are essential.…”
Section: Discussionmentioning
confidence: 76%
“…[11][12][13][14][15] CRP concentrations at ICU discharge in our patients were not as useful in predicting adverse events as previously reported. This may be explained by a large proportion of elective admissions (42%) with a lower acuity illness compared to previous studies.…”
Section: Accepted M Manuscriptmentioning
confidence: 70%
“…[7][8] Although some prognostic scores have been shown to predict post-ICU readmission and mortality [9][10], many of these scores are difficult to estimate at the bedside, and as such, most practising clinicians still rely on subjective assessment of their patients to determine whether their patients are suitable for ICU discharge. [11] Recurrent or persistent infection and inflammation may play a role in leading to unexpected readmission or mortality after ICU discharge. This hypothesis is supported by the fact that inflammatory markers such as C-reactive protein (CRP) and white blood cell count at ICU discharge were more likely to be elevated among those who were subsequently readmitted compared to those without readmission.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…53 With increased ICU bed supply, patients who are not critically ill and those who are unlikely to survive regardless of ICU care may nevertheless be admitted to ICUs, 54 highlighting the need for policies that incentivize the judicious use of ICU resources. Avoiding delays in transfer from the ICU to regular nursing floors 55,56 and appropriate initiation of palliative care may also reduce costs.…”
Section: Discussionmentioning
confidence: 99%